Analysis of Flow and Thermal Performance of Sio2- Water Nanofluids with Variable Geometrical and Process Parameters - N. Oumer, H. Wan Azmi, Azizuddin Abd Aziz, J. P. Siregar, Aklilu T. Baheta (Mathematical Statistician and Engineering Applications, 2022)
This study numerically investigated the thermal-hydraulic performances of a single-phase SiO2-water nanofluid in forced convective turbulent flow in a pipe. The nanoparticle volume concentrations varied from 0-4% by weight. At different Res, bulk temperatures, and particle sizes, simulations were run. The obtained results showed that, in comparison to other input parameters, nanoparticle concentration and inlet velocity considerably affect the heat transfer coefficient (h) and pressure drop (. The analysis of thermal and flow performance discovered that increasing the nanoparticle concentration and inflow velocity significantly improves the ( and h.